Evolution of high-altitude river-dominated lake deltas, NW Himalaya - Sumit Sagwal; Anil Kumar; Subhojit Saha; Gautam Rawat; Pradeep Srivastava; Choudhurimayum Pankaj Sharma (CATENA, 2026)

Lactobionic acid-enriched yoghurt improves calcium bioavailability and bone mineralization: in vitro and in vivo validation - Shamim Hossain; Yogesh Khetra; Chandni Dularia; Sangita Ganguly; Himanshu Kumar Singh; Sumit Arora; Heena Sharma (Bioactive Carbohydrates and Dietary Fibre, 2026)

Machine learning modeling of cadmium adsorption on engineered biochar using optimized gradient boosting decision trees - Ahmad Adel Abu-Shareha; Raed Alfilh; Araa Mohammed Yaseen; Gadug Sudhamsu; Prabhat Kumar Sahu; Roselin Jenifer D; Sumit Sharma; Vatsal Jain; Zarghuna Hekmatyar (Waste Disposal & Sustainable Energy, 2026)

Hydrothermal Liquefaction-Based extraction of biogenic silica and biocrude from diatoms cultivated in rice straw hydrolysate - Sumit Dhali; Anushree Malik; Satyawati Sharma; Ramesh Raliya (Bioresource Technology, 2026)

Bacopa monnieri and Alzheimer’s disease: mechanistic convergence, cognitive outcomes and translational perspectives - Ankita Kumawat; Madan Mohan Sharma; Sumit Nathani (Inflammopharmacology, 2026)

Shaping SHAPE - A spectro-polarimeter onboard Chandrayaan-3 to observe Earth as an Exoplanet - Anuj Nandi; Swapnil Singh; Bhavesh Jaiswal; Anand Jain; Smrati Verma; Reenu Palawat; B.T. Ravishankar; Brajpal Singh; Priyanka Das; Supratik Bose; Supriya Verma; Waghmare Rahul Gautam; et al. (Advances in Space Research, 2026)

Bioefficacy of plant growth promoting rhizobacteria (PGPR) in the sustainable management of root-knot nematodes in eggplant - Megha Sharma; Sunita Devi; Sumit Vashisth; Dharmendra Kumar; Subhash Chand; Kumari Manorma; Rakesh Kumar; Parmod Verma; Balbir Singh Dilta; Abhay (Physiological and Molecular Plant Pathology, 2026)

Harnessing hemicellulose: A systematic review of its role in bioethanol and value-added product synthesis from lignocellulosic feedstocks - Diksha Sawhney; Sumit Sharma; Meenu Singh; Prabhat Kumar; Roma Pandey (Bioresource Technology Reports, 2026)

Unveiling the glucan profile: a comparative study of Lion’s Mane and Shiitake mushrooms - C. S. Keerthana; Rozy Kumari; Muskan Beura; Sumit Sharan; Susheel Kumar Sharma; Ananta Ganjoo; Anil Dahuja; Veda Krishnan (Natural Product Research, 2026)

Influence of calcium-chelating salts on mineral-equilibria and techno-functional properties of buffalo milk - Mamta Vaishnav; Sumit Arora; Richa Singh; Shaik Abdul Hussain; Vivek Sharma; Utkarsh Deshmukh (International Dairy Journal, 2026)

Effect of sodium hexametaphosphate and trisodium citrate on the heat stability, rheological and functional properties of microfiltered retentate of buffalo milk - Bhaskara K. Govindappa; Bhumkar Prajwal Vilas; Ganga Sahay Meena; Sumit Arora; Heena Sharma; Ashish Kumar Singh; Gaurav Kr Deshwal (International Dairy Journal, 2026)

Integrated chemo-enzymatic strategy for production of functional xylooligosaccharides from sunflower stalk biomass - Mahak Gupta; Ridhika Bangotra; Surbhi Sharma; Bisma Habib; Arpana Thakur; Priya Singh; Muskaan Chib; Parushi Nargotra; Vishal Sharma; Nisha Kapoor; Ritu Mahajan; Sumit G. Gandhi; et al. (World Journal of Microbiology and Biotechnology, 2026)

Human reproductive exposure to microplastics: A multi-technique analytical study of menstrual and amniotic fluids - Girish Chandra Sharma; Neeraj Kumar; Damini Devrukhkar; Rahul Mulchandji Joshi; Sourav Debnath; Bhumi Chaturvedi; Sumit Rajotiya; Shivang Mishra; Anupama Sharma; Mahaveer Singh; Deepak Nathiya; Balvir Singh Tomar (NanoImpact, 2026)

Reliable Model Development of Density for Pure Biofuels via Data Driven Approaches - Mahran Al-Zyoud; Magdi E. A. Zaki; Raed Alfilh; Gadug Sudhamsu; Prabhat Kumar Sahu; Murari Devakannan Kamalesh; Sumit Sharma; Sobhi M. Gomha; Nargis Yousafzai (BioEnergy Research, 2026)

Bio-inspired alternatives in construction for a green built environment: a review - Sumit Sharma; Hamidreza Shapouri (Innovative Infrastructure Solutions, 2026)

Harnessing teosinte for quality traits enhancement and genetic diversity in maize - Pardeep Kumar; Mukesh Choudhary; Seema Sheoran; Bhupender Kumar; Sushil Kumar; Ankush Sharma; Bharat Bhushan; Bahadur Singh Jat; Dharam Paul; Sumit Kumar Aggarwal; Shyam Bir Singh (Cereal Research Communications, 2026)

Unravelling the role of soil enzymatic activity as a vital bioindicator of soil health and fertility in agricultural systems - Ingudam Bhupenchandra; L. Devarishi Sharma; Menaka Devi Salam; Sumit Kumar; S.K. Chongtham; Anil K. Choudhary; H. Lembisana Devi; Soibam Sinyorita; Pranab Dutta; Ali Chenari Bouket; Tatiana Minkina; Chetan Keswani (Applied Soil Ecology, 2026)

Biological green synthesis of nanoparticles: A sustainable platform for agricultural, environmental, food, and cosmetic applications - Shruti S. Raut; Arpit Sharma; Ravi Yadav; Sumit Kumar; Alok Shukla; Amit Singh; Abha Mishra (Journal of Environmental Chemical Engineering, 2026)

Synergy between Piriformospora Indica and Salicylic Acid Modulates Maize Stress Physiology, Ultrastructure, and Gene Expression - Sunil K. Singh; Rakesh Pandey; Chanda Panwar; Pankaj Kumar; Sumit Sharma; Sonali Batra; Pradeep Kumar; Jai Gopal Sharma; Madhulika Singh; Bhoopander Giri (Journal of Plant Growth Regulation, 2026)

Advanced integrated Eco-strategies for effective antibiotic waste management - Varsha Sharma; Ishfaq Nabi Najar; Anu Radha; Sonali Sharma; Sunil Kumar; Deepika Singh; Sumit G. Gandhi; Vinod Kumar (Biodegradation, 2026)

Mechanisms and modalities of herbal anti-fertility: toward integrative reproductive health solutions - Manoj Kumar Mishra; Sumit Sharma; Shivangi Sharma; Sagar Pamu (Advances in Traditional Medicine, 2025)

Spatio-temporal variability of Quaternary glaciation in the arid alpine Spiti basin, Trans-Himalaya: Insights from luminescence dating and sedimentological analyses - Uday Sharma; Yogesh Ray; Sumit Sagwal; Satish J. Sangode (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Influence of multi-enzyme approach and spray drying on physico-chemical, browning and protein digestibility of lactose-hydrolyzed milk powder - Payal Singh; Sumit Arora; Deepika Kathuria; Richa Singh; Priyanka Singh Rao; Vivek Sharma; Ashish Kumar Singh (Food and Humanity, 2025)

Use of Different Organic Sources of Nutrients and Azotobacter for Enhancing Fruit Quality and Yield of Dragon Fruit - Sumit Bura; Amit Jasrotia; Arti Sharma; Deep Ji Bhat; Gurdev Chand; Anil Bhat; Ranbir Singh; Deepak Khatri; Aman (Applied Fruit Science, 2025)

Mitigating dust deposition effects on solar panels: an experimental approach using hydrophobic coating and vibration - Himanshu Kumar; Sandeep Yadav; Abhilasha Chaudhary; Sumit Sharma; Anita Kuradiya (Environmental Science and Pollution Research, 2025)

Influence of seasonal changes on the positional distribution of fatty acids in milk fat triglycerides of indigenous cow (sahiwal) and crossbred cow (Karan Fries) - Pavel Rout; Vivek Sharma; Sumit Arora; Rajeev Kapila; A.K. Singh (International Dairy Journal, 2025)

Antimicrobial activity of ethnomedicinal plants used by indigenous tribes of Southern Rajasthan districts of India to treat gastrointestinal diseases - Acharya Balkrishna; Hemant Sharma; Sonam Verma; Sumit Kumar Singh; Vidhi Dobhal; Vedpriya Arya (Next Research, 2025)

Advances in CRISPR/Cas9-driven strategies for microbial production and optimization of sugar polyols for food applications: A review - Manoj Kumar; Sumit Totade; Kanika Sharma; Ajinath Dukare; K. Pandiyan; Sujata Saxena (Food Bioscience, 2025)

Impact of indoor plant-induced relative humidity on PM concentration in indoor urban environment - Supreet Kaur; Sumit Kumar Mishra; Vikas Goel; Mayank Kumar; Rishabh Singh; Mamta Devi; Harish Chandra; Vijayan Narayanasamy; S.P. Singh; Parag Sharma; Prashant Kumar (Atmospheric Pollution Research, 2025)

Integrating climate, air, and health goals: the impact of efficient cooling policies in India - Shivang Agarwal; Gaurav Phore; Manjeet Singh; Nimish Singh; Shivani Sharma; Mani Juneja; Karan Mangotra; Sumit Sharma (Journal of Environmental Studies and Sciences, 2025)

Investigating the possibility of using waste plastic fuel and gasoline fuel mixture in gasoline direct injection engine through experimental studies and the Taguchi method - Sumit Kanchan; Abhishek Mukhija; Subhash Sharma; Rohitash Choudhary; Rajesh Choudhary; Ravinder Kumar (Fuel, 2025)

Role of surface functional groups in the adsorption behavior of microcystin-LR on graphene surfaces - Hemant Nagar; Sumit Sharma (Chemosphere, 2025)

Efficacy of salicylic acid (SA) in modulating the dynamics of pesticide-thiamethoxam-induced stress responses in Brassica juncea L. insights from biochemical and molecular dissection - Arun Dev Singh; Nancy Sharma; Kamini Devi; Jaspreet Kour; Sumit G. Gandhi; Renu Bhardwaj; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Environmental Pollution, 2025)

Impact of polysaccharide addition on the technological aspects of low lactose milk powders - Chandrakanta Sen; Sumit Arora; Richa Singh; Vivek Sharma; Ganga Sahay Meena; Ashish Kumar Singh (Food Research International, 2025)

Anti-adipogenic and anti-steatotic potential of edible pigment bixin and annatto seed extracts: LC-MS based bioactive profiling and in vitro biochemical validation - Sonakshi Puri; Sumit Kumar Mandal; Tripti Joshi; Nikita; Ayush Srivastava; Pankaj Kumar Sharma; P.R. Deepa (Food Bioscience, 2025)

Performance assessment of solar PV panels under varying environmental conditions: a laboratory and field-based approach for sustainable energy in mining operations - Abhishek Kumar Tripathi; Mangalpady Aruna; Sumit Sharma; Chandan Kumar; Mukesh Didwania (Environmental Science and Pollution Research, 2025)

Biosimilars: A Critical Review of Development, Regulatory Landscape, and Clinical Implications - Ankit Monga; Gagan; Pragya Jamwal; Sumit Sharma; Amanpreet Kaur (AAPS PharmSciTech, 2025)

Combined application of earthworms and plant growth promoting rhizobacteria improve metal uptake, photosynthetic efficiency and modulate secondary metabolites levels under chromium metal toxicity in Brassica juncea L - Pooja Sharma; Palak Bakshi; Rekha Chouhan; Sumit G. Gandhi; Rupinder Kaur; Ashutosh Sharma; Renu Bhardwaj; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Hazardous Materials, 2025)

Modeling sediment flow analysis for hydro-electric projects using deep neural networks - Sagar Tomar; Asheesh Sharma; Aabha Sargaonkar; Sumit Malwal; Shrey Gupta; Kishor S. Kulkarni; Rajesh Biniwale (Earth Science Informatics, 2025)

Predicting river sediment deposition using machine learning and InVEST-SDR modeling- A hydro electric perspective - Aryan Tyagi; Sagar Tomar; Kishor S. Kulkarni; Shilpa Sharma; Alisha Raut; Sumit Malwal (Earth Science Informatics, 2025)

In silico design and assessment of a multi-epitope peptide vaccine against multidrug-resistant Acinetobacter baumannii - Shiv Nandan Sah; Sumit Gupta; Neha Bhardwaj; Lalit Kumar Gautam; Neena Capalash; Prince Sharma (In Silico Pharmacology, 2024)

Plant-derived biochar and salicylic acid as biostimulants for Lycopersicon esculentum under chromium toxicity conditions: Insights from physiochemical attributes, antioxidants, and relative gene expression - Kamini Devi; Sahaurti Sharma; Arun Dev Singh; Tamanna Bhardwaj; Sumit G. Gandhi; Puja Ohri; Renu Bhardwaj; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Environmental Chemical Engineering, 2024)

Developing low-lactose milk powder: A multi-enzyme approach to reduce Maillard browning - Payal Singh; Sumit Arora; Deepika Kathuria; Richa Singh; Priyanka Singh Rao; Vivek Sharma (Innovative Food Science & Emerging Technologies, 2024)

In search of poly-3-hydroxybutyrate (PHB): A comprehensive review unveiling applications and progress in fostering a sustainable bio-circular economy - Ishfaq Nabi Najar; Prayatna Sharma; Rohit Das; Krishnendu Mondal; Ashish Kumar Singh; Sonia Tamang; Palash Hazra; Nagendra Thakur; Rajendra Bhanwaria; Sumit G Gandhi; Vinod Kumar (Food and Bioproducts Processing, 2024)

Multi-omics analysis reveals the positive impact of differential chloroplast activity during in vitro regeneration of barley - Parul Sirohi; Chanderkant Chaudhary; Mayank Sharma; Ravi Bodampalli Anjanappa; Suchi Baliyan; Ritika Vishnoi; Sumit Kumar Mishra; Reeku Chaudhary; Bhairavnath Waghmode; Anuj Kumar Poonia; Hugo Germain; Debabrata Sircar; et al. (Plant Molecular Biology, 2024)

Hydrogen peroxide mediated thermo-catalytic conversion of carbon dioxide to C1-C2 products over Cu (0) - Vishrant Kumar; Nicky Kumar Lamba; Aamir Baig; Amit Kumar Sonker; Nikhil Sharma; Jaidev Kaushik; Kumud Malika Tripathi; Sonal; Sumit Kumar Sonkar (Chemical Engineering Journal, 2024)

Long term analysis of air quality parameters for Ludhiana, India: sources, trends and health impact - Ankita Buwaniwal; Veena Sharma; Gagan Gupta; Sumit Rohj; Sandeep Kansal (Environmental Geochemistry and Health, 2024)

Involvement of Sirt1-FoxO3a-Bnip3 axis and autophagy mediated mitochondrial turnover in according protection to hyperglycemic NRK-52E cells by Berberine - Sugandh Saxena; Sumit Kumar Anand; Ankita Sharma; Poonam Kakkar (Toxicology in Vitro, 2024)

Nanocellulose-based porous lightweight materials with flame retardant properties: A review - Shariful Islam Tushar; Habibur Rahman Anik; Md Mazbah Uddin; Sumit Mandal; Vijay Mohakar; Smriti Rai; Suraj Sharma (Carbohydrate Polymers, 2024)

Characterization and utilization of algal and wheat husk biochar as biofertilizers for sustainable soil amelioration - Sharma Mona; Neha Saini; Sujata; Sumit Kumar; Anuj Sharma; Anjali Yadav; Navita Yadav; Bansal Deepak (Bioresource Technology Reports, 2024)

Effect of Methyl Jasmonate and Salicylic Acid on the Enrichment of Carbazole Alkaloids in Murraya koenigii (L.) Spreng - Sumit Kumar Singh; Gaurav Sharma; Pratibha Singh; Sanjeev K. Shukla; Sanjeev Kanojiya; Dipak Kumar Mishra (Journal of Plant Growth Regulation, 2024)

Microbial diversity associated with the natural spring water of Western Himalayas - Yukti Oza; Mrunal Karande; Rochita Ghosh; Janhvi Mishra Rawat; Sumit Purohit; Balwant Rawat; Alimuddin Zumla; Avinash Sharma (Vegetos, 2024)

From waste management to circular economy: Leveraging thermophiles for sustainable growth and global resource optimization - Ishfaq Nabi Najar; Prayatna Sharma; Rohit Das; Sonia Tamang; Krishnendu Mondal; Nagendra Thakur; Sumit G. Gandhi; Vinod Kumar (Journal of Environmental Management, 2024)

Targeting lipid-sensing nuclear receptors PPAR (α, γ, β/δ): HTVS and molecular docking/dynamics analysis of pharmacological ligands as potential pan-PPAR agonists - Sumit Kumar Mandal; Sonakshi Puri; Banoth Karan Kumar; Mohammed Muzaffar-Ur-Rehman; Pankaj Kumar Sharma; Murugesan Sankaranarayanan; P. R. Deepa (Molecular Diversity, 2024)

In vitro propagation of Bergenia stracheyi: an alternative approach for higher production of valuable bioactive compounds - Awzia Amin; Nancy Sharma; Phalisteen Sultan; Sumit G. Gandhi; Kota Srinivas; Qazi Parvaiz Hassan; Zabeer Ahmed (Vegetos, 2024)

A green and economic approach to synthesize magnetic Lagenaria siceraria biochar (γ-Fe2O3-LSB) for methylene blue removal from aqueous solution - Ayushi Mishra; Jyoti Pandey; Himanshu Ojha; Malti Sharma; Lajpreet Kaur; Akhilesh Pandey; Pankaj Sharma; Sumit Murab; Rahul Singhal; Mallika Pathak (Environmental Science and Pollution Research, 2024)

Reduction of maillard browning in spray dried low-lactose milk powders due to protein polysaccharide interactions - Chandrakanta Sen; Sumit Arora; Richa Singh; Vivek Sharma; Ganga Sahay Meena; Ashish Kumar Singh (Food Research International, 2024)

A simulacrum of proliferative vitreoretinopathy (PVR): development and proteomics-based validation of an in vitro model - Sumit Sharma; Amit Kumar Thakur; Maryada Sharma; Deeksha Katoch; Reema Bansal; Ramandeep Singh; Mangat R. Dogra; Manni Luthra-Guptasarma (Journal of Proteins and Proteomics, 2024)

Semecarpus anacardium L.f. leaf extract exhibits activities against breast cancer and prolongs the survival of tumor-bearing mice - Rajesh Kumar Singh; Bhagaban Mallik; Amit Ranjan; Ruchita Tripathi; Sumit Singh Verma; Vinamra Sharma; Subash Chandra Gupta; Anil Kumar Singh (Natural Product Research, 2024)

Metarhabditis amsactae: A potential biopesticide isolated from Punjab (India) with potent insecticidal activity and immunomodulatory effects against Galleria mellonella (Lepidoptera: Pyralidae) - Sandeep Kour; Nancy Sharma; Randeep Singh; Sumit G. Gandhi; Puja Ohri (Journal of Invertebrate Pathology, 2024)

Optimization of Virus-induced Phytoene Desaturase (PDS) gene silencing using Tobacco Rattle Virus in Coleus forskohlii - Archana Bhat; Sahaurti Sharma; Sumit G. Gandhi (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Influence of calcium depletion and addition on heat stability, buffering capacity, partitioning of minerals and iron binding properties of buffalo milk - Utkarsh Deshmukh; Sumit Arora; Deepika Kathuria; A.K. Singh; Vivek Sharma; Richa Singh (International Dairy Journal, 2024)

Effect of depolymerized lignin on the cellulosic/hemicellulosic precursors for fungal secondary metabolite (kojic acid) production - Sumit Sharma; Shikha Singh; Saurabh Jyoti Sarma (Bioresource Technology Reports, 2024)

Bibliometric analysis, physical properties, and experimental evaluation of additives-diesel ternary blends - Chandan Kumar; Mukesh Kumar; Umesh Kumar Das; Sumit Sharma (Environmental Science and Pollution Research, 2023)

Nutraceutical and flavor profiles in underutilized desert legumes of India: gene editing strategies towards sustainable food development - Tripti Joshi; Hansa Sehgal; Sumit Kumar Mandal; Mukul Joshi; P. R. Deepa; Pankaj Kumar Sharma (Journal of Plant Biochemistry and Biotechnology, 2023)

Development of yeast aerobic granules for long-term continuous bioethanol production from rice straw hydrolysate - Sumit Sharma; Shikha Singh; Saurabh Jyoti Sarma; Mohammad Danish (Fuel, 2023)

A graphene-based material for green sustainable energy technology for hydrogen storage - Nibedita Nath; Subhendu Chakroborty; Sumit Sharma; Abhishek Sharma; Anil Singh Yadav; Tabish Alam (Environmental Science and Pollution Research, 2023)

Modelling efficiency of fluid viscous dampers positioning for increasing tall buildings' Resilience to earthquakes induced structural vibrations - Kul Vaibhav Sharma; Viral Parmar; Lilesh Gautam; Sumit Choudhary; Jigar Gohil (Soil Dynamics and Earthquake Engineering, 2023)

An atypical heterotrimeric Gα and its interactome suggest an extra-large role in overcoming abiotic and biotic stress - Bhawana Sharma; Jahanvi Ganotra; Brijesh Biswal; Kanishka Sharma; Sumit Gandhi; Deepak Bhardwaj; Narendra Tuteja (Physiology and Molecular Biology of Plants, 2023)

Arid/semi-arid flora as a treasure trove of bioactives and bioenergy: the case for underutilized desert legumes towards environmental sustainability - Tripti Joshi; Sumit Kumar Mandal; Vidushi Asati; Perinkulam Ravi Deepa; Pankaj Kumar Sharma (Environmental Science and Pollution Research, 2023)

Informing watershed management in data-scarce Indian Himalayas - Bhargabnanda Dass; Denzil Daniel; Nishant Saxena; Anita Sharma; Debashish Sen; Sumit Sen (Water Security, 2023)

Rottlerin renders a selective and highly potent CYP2C8 inhibition to impede EET formation for implication in cancer therapy - Diksha Manhas; Shipra Bhatt; Garima Rai; Vinay Kumar; Sahil Bharti; Sumit Dhiman; Shreyans K. Jain; Deepak K. Sharma; Probir Kumar Ojha; Sumit G. Gandhi; Anindya Goswami; Utpal Nandi (Chemico-Biological Interactions, 2023)

Streamlining Food Effect Assessment — Are Repeated Food Effect Studies Needed? An IQ Analysis - Filippos Kesisoglou; Sumit Basu; Tejashree Belubbi; Philip Bransford; John Chung; Stephanie Dodd; Michael Dolton; Tycho Heimbach; Priyanka Kulkarni; Wen Lin; Andrea Moir; Neil Parrott; et al. (The AAPS Journal, 2023)

Challenges and advancements in bioprocess intensification of fungal secondary metabolite: kojic acid - Sumit Sharma; Shikha Singh; Saurabh Jyoti Sarma (World Journal of Microbiology and Biotechnology, 2023)

Influence of Nanocarrier Type on the Drug Delivery Aspects of Docetaxel: Empirical Evidences - Saad M. Alshahrani; Nagarani Thotakura; Saurabh Sharma; Sheikh Shahnawaz Quadir; Nishtha Chaurawal; Sumit Sharma; Deepak Chitkara; Kaisar Raza (Journal of Pharmaceutical Innovation, 2023)

Interactive effect of 24-epibrassinolide and plant growth promoting rhizobacteria inoculation restores photosynthetic attributes in Brassica juncea L. under chlorpyrifos toxicity - Palak Bakshi; Pooja Sharma; Rekha Chouhan; Bilal Ahmad Mir; Sumit G. Gandhi; Renu Bhardwaj; Pravej Alam; Parvaiz Ahmad (Environmental Pollution, 2023)

High-Resolution Mapping of Air Pollution in Delhi Using Detrended Kriging Model - Md H. Rahman; Shivang Agarwal; Sumit Sharma; R. Suresh; Seema Kundu; Stijn Vranckx; Bino Maiheu; Lisa Blyth; Stijn Janssen; Sousa Jorge; Prashant Gargava; V. K. Shukla; et al. (Environmental Modeling & Assessment, 2023)

Microbial Population Dynamics in Lemnaceae (Duckweed)-Based Wastewater Treatment System - Pooja Singh; Kunal Jani; Shreyansh Sharma; Vinay Rale; Yogesh Souche; Sumit Prakash; Prasanna Jogdeo; Yogesh Patil; Manikprabhu N. Dhanorkar (Current Microbiology, 2023)

Cow-urine emulsified diesel fuel: preparation, stability, and rheological study for diesel engine application - Amit Jhalani; Sumit Sharma; Digambar Singh; Pushpendra Kumar Sharma (Environmental Science and Pollution Research, 2022)

Recent trends of green human resource management: Text mining and network analysis - Chetan Sharma; Sumit Sakhuja; Shivinder Nijjer (Environmental Science and Pollution Research, 2022)

Avian Haemosporidian (Plasmodium and Haemoproteus) Status in Two Bird Groups (Old-World Flycatchers and Thrushes) of India and Their Phylogenetic Relationships with Other Lineages of the World - Vipin; Ashutosh Singh; Vinita Sharma; Narinder Kumar Tripathi; Rajnikant Dixit; Bhim Singh; Chandra Prakash Sharma; Sumit G. Gandhi; Dhananjai Mohan; Sandeep Kumar Gupta (Acta Parasitologica, 2022)

An integration of health risk indices and statistical techniques to appraise the associated human risks and source apportionment of potentially toxic elements in roadside soils - Vinod Kumar; Shevita Pandita; Sumit Singh; Anket Sharma (Arabian Journal of Geosciences, 2022)

Improved skill of NCMRWF Unified Model (NCUM-G) in forecasting tropical cyclones over NIO during 2015–2019 - Sushant Kumar; Anumeha Dube; Sumit Kumar; S Indira Rani; Kuldeep Sharma; S Karunasagar; Saji Mohandas; Raghavendra Ashrit; John P George; Ashis K Mitra (Journal of Earth System Science, 2022)

Review on performance assessment of solar stills using computational fluid dynamics (CFD) - Danduprolu Purnachandrakumar; Gaurav Mittal; Ram K. Sharma; Desh Bandhu Singh; Sumit Tiwari; Harender Sinhmar (Environmental Science and Pollution Research, 2022)

A novel seasonal index–based machine learning approach for air pollution forecasting - Adeel Khan; Sumit Sharma; Kaushik Roy Chowdhury; Prateek Sharma (Environmental Monitoring and Assessment, 2022)

Study of variation of aerosol optical properties over a high altitude station in Indian Western Himalayan region, palampur using raman lidar system - Shishir Kumar Singh; S. R. Radhakrishnan; Jaswant; Sumit Kumar Mishra; Devesh Kumar Shukla; Ashish Ranjan; Chhemendra Sharma (Journal of Atmospheric Chemistry, 2022)

Rapid determination and optimisation of berberine from Himalayan Berberis lycium by soxhlet apparatus using CCD-RSM and its quality control as a potential candidate for COVID-19 - Anil Kumar Katare; Bikarma Singh; Pooja Shukla; Sandeep Gupta; Bishander Singh; Kavya Yalamanchili; Nitin Kulshrestha; Rajendra Bhanwaria; Ashok Kumar Sharma; Sarita Sharma; Sneha; Durga Prasad Mindala; et al. (Natural Product Research, 2022)

NMR-based metabolomic profiling of the differential concentration of phytomedicinal compounds in pericarp, skin and seeds of Momordica charantia (bitter melon) - Sumit Mishra; Ankit; Rakesh Sharma; Navdeep Gogna; Kavita Dorai (Natural Product Research, 2022)

Comparative study on detection efficacy of universal potyviruses primers - Abhishek Sharma; Shikha Sharma; Irfan Khan; Sukhjeet Kaur; Sumit Inder Kaur (Vegetos, 2021)

Establishment of virus-free elite mother orchards of apple in the Trans-Himalayan region of India - Santosh Watpade; Rakesh Kumar; Pooja Bhardwaj; Kallol Kumar Pramanick; Arun Kumar Shukla; Baswaraj Raigond; Jitender Kumar; Usha Sharma; Sumit Vashisth; Sudhir Verma (Indian Phytopathology, 2021)

Isolation optimisation, synthesis, molecular docking and in silico ADMET studies of lantadene a and its derivatives - Sharad Kumar Suthar; Ajay Hooda; Ankesh Sharma; Sumit Bansal; Jitender Monga; Monika Chauhan; Manu Sharma (Natural Product Research, 2021)

Recommended Best Practices for Lyophilization Validation 2021 Part II: Process Qualification and Continued Process Verification - Feroz Jameel; Alina Alexeenko; Akhilesh Bhambhani; Gregory Sacha; Tong Zhu; Serguei Tchessalov; Puneet Sharma; Ehab Moussa; Lavanya Iyer; Sumit Luthra; Jayasree Srinivasan; Ted Tharp; et al. (AAPS PharmSciTech, 2021)
This work describes the lyophilization process validation and consists of two parts. Part one (Part I: Process Design and Modeling) focuses on the process design and is described in the previous paper, while the current paper is devoted to process qualification and continued process verification. The goal of the study is to show the cutting edge of lyophilization validation based on the integrated community-based opinion and the industrial perspective. This study presents best practices for batch size determination and includes the effect of batch size on drying time, process parameters selection strategies, and batch size overage to compensate for losses during production. It also includes sampling strategies to demonstrate batch uniformity as well as the use of statistical models to ensure adequate sampling. Based on the LyoHUB member organizations survey, the best practices in determining the number of PPQ runs are developed including the bracketing approach with minimum and maximum loads. Standard practice around CQA and CPP selection is outlined and shows the advantages of using control charts and run charts for process trending and quality control. The case studies demonstrating the validation strategy for monoclonal antibody and the impact of the loading process on the lyophilization cycle and product quality as well as the special case of lyophilization for dual-chamber cartridge system are chosen to illustrate the process validation. The standard practices in the validation of the lyophilization process, special lyophilization processes, and their impact on the validation strategy are discussed. Graphical Abstract

Evaluation of the benefits of assimilation of Meteosat-8 observations in an NWP system over the Indian Ocean region - M. T. Bushair; S. Indira Rani; Buddhi Prakash Jangid; Priti Sharma; Sumit Kumar; John. P. George; M. Das Gupta (Meteorology and Atmospheric Physics, 2021)

Isolation and biochemical characterization of a novel serine protease identified from solid tannery waste metagenome - Sumit Kumar Verma; Prakash Chand Sharma (Biologia, 2021)

Application of virus-induced gene silencing in Andrographis paniculata, an economically important medicinal plant - Anchal Garg; Shubha Sharma; Payal Srivastava; Sumit Ghosh (Protoplasma, 2021)

Role of vitamins and minerals as immunity boosters in COVID-19 - Puneet Kumar; Mandeep Kumar; Onkar Bedi; Manisha Gupta; Sachin Kumar; Gagandeep Jaiswal; Vikrant Rahi; Narhari Gangaram Yedke; Anjali Bijalwan; Shubham Sharma; Sumit Jamwal (Inflammopharmacology, 2021)

Unraveling the AM fungal community for understanding its ecosystem resilience to changed climate in agroecosystems - Dipanti Chourasiya; Manju M. Gupta; Sumit Sahni; Fritz Oehl; Richa Agnihotri; Reena Buade; Hemant S Maheshwari; Anil Prakash; Mahaveer P Sharma (Symbiosis, 2021)

Structural characterization and functional annotation of microbial proteases mined from solid tannery waste metagenome - Sumit K. Verma; Simerpreet Kaur; Arnav Tevetia; Sayan Chatterjee; Prakash C. Sharma (Biologia, 2021)

A Comprehensive Review on 1st-Generation Biodiesel Feedstock Palm Oil: Production, Engine Performance, and Exhaust Emissions - Digambar Singh; Dilip Sharma; S. L. Soni; Chandrapal Singh Inda; Sumit Sharma; Pushpendra Kumar Sharma; Amit Jhalani (BioEnergy Research, 2021)

Principal component based fusion of land surface temperature (LST) and panchromatic (PAN) images - Kul Vaibhav Sharma; Sumit Khandelwal; Nivedita Kaul (Spatial Information Research, 2021)

Comparative Assessment of Vegetation Indices in Downscaling of MODIS Satellite Land Surface Temperature - Kul Vaibhav Sharma; Sumit Khandelwal; Nivedita Kaul (Remote Sensing in Earth Systems Sciences, 2020)

Secretor Status is Associated with Susceptibility to Disease in a Large GII.6 Norovirus Foodborne Outbreak - Sumit Sharma; Marie Hagbom; Beatrice Carlsson; Joanna Nederby Öhd; Mona Insulander; Ronnie Eriksson; Magnus Simonsson; Micael Widerström; Johan Nordgren (Food and Environmental Virology, 2020)
Norovirus is commonly associated with food and waterborne outbreaks. Genetic susceptibility to norovirus is largely dependent on presence of histo-blood group antigens (HBGA), specifically ABO, secretor, and Lewis phenotypes. The aim of the study was to determine the association between HBGAs to norovirus susceptibility during a large norovirus foodborne outbreak linked to genotype GII.6 in an office-based company in Stockholm, Sweden, 2015. A two-episode outbreak with symptoms of diarrhea and vomiting occurred in 2015. An online questionnaire was sent to all 1109 employees that had worked during the first outbreak episode. Food and water samples were collected from in-house restaurant and tested for bacterial and viral pathogens. In addition, fecal samples were collected from 8 employees that had diarrhea. To investigate genetic susceptibility during the outbreak, 98 saliva samples were analyzed for ABO, secretor, and Lewis phenotypes using ELISA. A total of 542 of 1109 (49%) employees reported gastrointestinal symptoms. All 8 fecal samples tested positive for GII norovirus, which was also detected in coleslaw collected from the in-house restaurant. Eating at the in-house restaurant was significantly associated with risk of symptom development. Nucleotide sequencing was successful for 5/8 fecal samples and all belonged to the GII.6 genotype. HBGA characterization showed a strong secretor association to norovirus-related symptoms ( P = 0.014). No association between norovirus disease and ABO phenotypes was observed. The result of this study shows that non-secretors were significantly less likely to report symptoms in a large foodborne outbreak linked to the emerging GII.6 norovirus strain.

Occurrence of pepper mottle virus on tomato in India - Shikha Sharma; Abhishek Sharma; Sumit Inder Kaur (VirusDisease, 2019)

Radiation hazards associated with radionuclides and theoretical evaluation of indoor radon concentration from soil exhalation of Udhampur District, Jammu and Kashmir State, India - Sumit Sharma; Ajay Kumar; Rohit Mehra; Rosaline Mishra (Journal of Soils and Sediments, 2019)

A comprehensive review on water-emulsified diesel fuel: chemistry, engine performance and exhaust emissions - Amit Jhalani; Dilip Sharma; Shyam Lal Soni; Pushpendra Kumar Sharma; Sumit Sharma (Environmental Science and Pollution Research, 2019)

Assessment of Soil Gas Radon and Exhalation Studies in Lower Himalayan Region of Jammu and Kashmir State, India - Sumit Sharma; Ajay Kumar; Rohit Mehra; Rosaline Mishra (Pure and Applied Geophysics, 2018)

Assessment of radionuclide concentration and exhalation studies in soil of lesser Himalayas of Jammu and Kashmir, India - Ajay Kumar; Raman Vij; Sumit Sharma; Amit Sarin; Saurabh Narang (Acta Geophysica, 2018)

Assessment of progeny concentrations of 222Rn/220Rn and their related doses using deposition-based direct progeny sensors - Sumit Sharma; Ajay Kumar; Rohit Mehra; Manpreet Kaur; Rosaline Mishra (Environmental Science and Pollution Research, 2018)

Assessment of radon concentration and heavy metal contamination in groundwater of Udhampur district, Jammu & Kashmir, India - Ajay Kumar; Sumit Sharma; Rohit Mehra; Priya Kanwar; Rosaline Mishra; Inderpreet Kaur (Environmental Geochemistry and Health, 2018)

Liquid Nanosize Emulsion-Filled Enteric-Coated Capsules for Colon Delivery of Immunosuppressant Peptide - Sumit Sharma; Vivek Ranjan Sinha (AAPS PharmSciTech, 2018)

Characterization of a bacterioferritin comigratory protein family 1-Cys peroxiredoxin from Candidatus Liberibacter asiaticus - Anamika Singh; Narender Kumar; Prabhat P. S. Tomar; Sumit Bhose; Dilip Kumar Ghosh; Partha Roy; Ashwani K. Sharma (Protoplasma, 2017)

Loop-mediated isothermal amplification (LAMP) based method for rapid and sensitive detection of ‘Candidatus Liberibacter asiaticus’ in citrus and the psyllid vector, Diaphorina citri Kuwayama - Dilip Kumar Ghosh; Sumit Bhose; Ashish Warghane; Manali Motghare; Ashwani Kumar Sharma; Arun Kumar Dhar; Siddarame Gowda (Journal of Plant Biochemistry and Biotechnology, 2016)

Emitter Uniformity and Application Efficiency for Centre‐ Pivot Irrigation Systems - Nithya Rajan; Stephan Maas; Rick Kellison; Monty Dollar; Song Cui; Sumit Sharma; Ahmed Attia (Irrigation and Drainage, 2015)
A significant portion of the intensively cultivated agricultural areas in the Southern Great Plains of the USA is located in the Texas High Plains. Agriculture in this region mainly depends on water from the vast underground Ogallala Aquifer. Due to excess withdrawal and a slow recharge process, groundwater levels are declining in many areas of the aquifer. Recently, regulations have been enacted in the Texas High Plains for restricting the amount of water pumped from the Ogallala Aquifer. In addition to pumping restrictions, conserving water by promoting irrigation systems with high application efficiency is also a priority. We investigated the emitted uniformity and application efficiency of 14 centre‐pivot irrigation systems in the Texas High Plains. Application efficiencies were in the range of 60–70% for mid‐elevation spray application (MESA) systems, 70–80% for low‐elevation spray application (LESA) systems, and greater than 90% for low‐energy precision application (LEPA) systems. Correction of the small number of defective emitters per system would not realize significant water savings. However, water savings could be realized by switching from MESA or LESA to LEPA, assuming the choice of crop allowed it. Copyright © 2015 John Wiley & Sons, Ltd.

Molecular docking and biological evaluation of hydroxy-substituted (Z)-3-benzylideneindolin-2-one chalcones for the lead identification as tyrosinase inhibitors - Sharad Kumar Suthar; Vaibhav Aggarwal; Monika Chauhan; Ankesh Sharma; Sumit Bansal; Manu Sharma (Medicinal Chemistry Research, 2015)

High rate of detection of G8P[6] rotavirus in children with acute gastroenteritis in São Tomé and Príncipe - Claudia Istrate; Sumit Sharma; Johan Nordgren; Sandra Videira e Castro; Ângela Lopes; João Piedade; Ahmed Zaky; António Lima; Edgar Neves; José Veiga; Aida Esteves (Archives of Virology, 2015)

Quantitative structure–activity relationship (QSAR) studies as strategic approach in drug discovery - Harun M. Patel; Malleshappa N. Noolvi; Poonam Sharma; Varun Jaiswal; Sumit Bansal; Sandeep Lohan; Suthar Sharad Kumar; Vikrant Abbot; Saurabh Dhiman; Varun Bhardwaj (Medicinal Chemistry Research, 2014)

Use of activated dry flowers (ADF) of Alstonia Scholaris for chromium (Vl) removal: equilibrium, kinetics and thermodynamics studies - Sumit Sharma; Navin Chandra Kothiyal (Environmental Science and Pollution Research, 2013)

Transcription of gD and gI genes in BHV1-infected cells - Sumit Chowdhury; Bhaskar Sharma (Journal of Biosciences, 2012)

Isolation and characterization of new compounds from seeds of Nigella sativa - Bhupendra Kumar Mehta; Uma Sharma; Sumit Agrawal; Vikas Pandit; Nidhi Joshi; Meenal Gupta (Medicinal Chemistry Research, 2008)

Evaluation of pentachlorophenol-degrading potentiality of Pseudomonas sp. in a soil microcosm - Sumit Kumar Gautam; Rajeev Sharma; A.H. Ahmad; Indu Shekhar Thakur (World Journal of Microbiology and Biotechnology, 2003)